Multi-Joint Dynamics and the Development of Movement Control - E. Otten (Neural Plasticity)
The movement control of articulated limbs in humans has been explained in terms of equilibrium points and moving equilibrium points or virtual trajectories. One hypothesis is that the nervous system controls multi-segment limbs by simply planning in terms of these equilibrium points and trajectories. The present paper describes a planar computer simulation of an articulated three-segment limb, controlled by pairs of muscles. The shape of the virtual trajectory is analyzed when the limb is required to make fast movements with endpoint movements along a straight line with bell-shaped velocity profiles. Apparently, the faster the movement, the more the virtual trajectory deviates from the real trajectory and becomes up to eight times longer. The complexity of the shape of the virtual trajectories and its length in these fast movements makes it unlikely that the nervous system plans using these trajectories. it seems simpler to set up the required bursts of muscle activation, coupled in the nervous system to the direction of movement, the s peed, and the place in workspace. Finally, it is argued that the two types of explanation do not contradict each other: when a relation is established in the nervous system between muscle activation and movements, equilibrium points and virtual trajectories are necessarily part of that relation.